A comprehensive DFT/TDDFT investigation into the influence of electron acceptors on the photophysical properties of ullazine-based D-π-A-π-A photosensitizers - Jing Huang; Zihao Li; Lei Yang; Rongfang Hu; Guoyu Shi (Scientific Reports)
Abstract The type of electron acceptor group has a significant effect on the photovoltaic properties of solar cell sensitizers. In this study, on the basis of previous studies of the π1- and π2-linked groups of D-π1-A1-π2-A2-type sensitizers, the photoelectric properties of Ullazine-Based photosensitizing dyes were further optimized by adjusting the electron-absorbing groups at the A1 and A2 positions. DFT and TDDFT calculations revealed that substituting the A1 position with a BTD moiety led to a substantial increase in the light absorption capacity of the dye. Furthermore, the incorporation of a CSSH moiety at the A2 position resulted in a significant redshift of the absorption spectrum and a notable increase in the light trapping efficiency. Moreover, TDM analysis indicates that HOMO→LUMO is the predominant mode of transition in the S0→S1 exciton transition of the dye molecule on the basis of the BTD motif. This mode remains the dominant mode after the introduction of the CSSH motif, although its contribution is reduced. Notably, HJ19 (A1 for BTD, A2 for CSSH) and HJ20 (A1 for difluorosubstituted BTD, A2 for CSSH) dyes demonstrate optimal optoelectronic properties, exhibiting redshifted absorption wavelengths by more than 79 nm and enhanced maximum absorption efficiencies by more than 40% with those of the YZ7 sensitizer.